LEAD ACCUMULATION IN MAIZE GRAINS, LEAVES AND OTHER PARTS OF THE PLANT: A POSSIBLE ROUTE FOR LEAD POISONING - CHIWETALU, UCHE; Egwuagu, Onyekachi; Ugwu , Kenneth Chikwado (FUDMA JOURNAL OF SCIENCES, 2022)
Lead (Pb) accumulation in parts of maize plant as a possible route for Pb poisoning was investigated. Experimental design adopted was a 3 factorial combination (4 x 1 x 1). Prior to planting of seeds, soil sample was analyzed for its physicochemical properties. At maturity, maize crop and parts of the plants were harvested and analyzed for their Pb contents. TF, BCF and BAF were as well determined. Physicochemical properties’ results revealed that pH was 6.75, Ec = 1.62 dSm-, K = 1.66 %, Mg =12.87 cmol/kg, Ca =1.9 cmol/kg, N = 0.6%, P = 0.98%, BD = 1.25 g/cm3 and MC = 40.84%. TF, BCF and BAF value obtained were < 1. Similarly, Pb found in the grains, leaves, shots, roots and soil were within 0.3133 - 1.0533 ppm; 4.7133 - 7.100 ppm; 8.070 - 14.09 ppm; 14.02 - 26.00 ppm and 172 - 551.34 ppm for grains, leaves, shoots, roots and soil Pb concentration respectively. However, consumption of vegetables and crops cultivated in Pb contaminated soil will pose serious health risk to the consumers as Pb found in the grain and leaves of maize were above the maximum permissible limit for health safety (0.2 ppm) recommended by joint FAO/WHO.
Keywords: Accumulation, Grain, Lead (Pb), Leaves, Maize, Poisoning